2016
DOI: 10.1248/cpb.c16-00060
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Thailandepsin B, a Potent HDAC Inhibitor Isolated from a Microorganism

Abstract: Thailandepsin B, a bicyclic depsipeptide histone deacetylase inhibitor, was efficiently synthesized in 51% overall yield in eight steps, starting from commercially available D-norleucine methyl ester and known (S,E)-3-(4-methoxybenzyloxy)-7-(tritylthio)hept-4-enoic acid. The method features a convergent approach in which the corresponding seco-acid, a key precursor in macrolactonization, is directly assembled through the condensation of a D-allo-isoleucine-D-cysteine-containing segment with a D-norleucine-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…Total syntheses of thailandepsin B have been reported by Cheng et al [13] . and Katoh et al [14] . The same group published the syntheses of Thailandepsins D –F [15]…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Total syntheses of thailandepsin B have been reported by Cheng et al [13] . and Katoh et al [14] . The same group published the syntheses of Thailandepsins D –F [15]…”
Section: Figurementioning
confidence: 99%
“…[1a] In accordance with ag eneral structure model for HDAC inhibitors proposedb yJ ung et al, [9] thailandepsins contain am acrocyclic backbone as cap group which is suggestedt ob eresponsible for enzymes pecificity.T he cap group is connected by an alkyl chain as spacer to the actual enzyme inhibiting warhead. Thailandepsins Aa nd Ch ave been synthesized by Ganesan et al, [10] Xu and Ye et al, [11] andK atoh et al [12] To tal syntheses of thailandepsinB have been reported by Cheng et al [13] and Katoh et al [14] The same group published the syntheses of Thailandepsins D-F. [15] In this work, we envisionedt he syntheses of thailandepsin B pseudo-natural products with varyingw arheads, for example, a hydroxamic acid (compound 8,S cheme 2). Thisf unctionality has shown to be ah ighly potent zinc-binding group.…”
mentioning
confidence: 99%
“…The carboxylic acid segments 16b can be utilized for the synthesis of FK228 (1) 9 and FR9001375 (2), 10b in which macrolactonization occurs via inversion of the C3′ stereochemistry. On the other hand, the carboxylic acid segments 34b-d can be used to synthesize spiruchostatin D (6), 13 burkholdacs A (7) and B (8), 14 and thailandepsins A-F (7-12), 15 in which the macrolactonization proceeds by retaining the C3′ stereochemistry.…”
Section: Scheme 2 Previously Reported Approaches On the Optically Actmentioning
confidence: 99%
“…The potentially therapeutic biological characteristics and unique structural features of 1-12 have made them attractive targets for total synthesis, and several such methods of synthesizing these natural products have been published in the literature. [9][10][11][12][13][14][15] Our previously reported synthetic pathway to FK228 (1) is outlined in Scheme 1 in a retrosynthetic fashion. 9a The method features the direct condensation of amine segment 14 and carboxylic acid segment 15 (or 16b) followed by the Mitsunobu macrolactonization of the corresponding secoacid 13 and intramolecular disulfide bond formation, which leads to the target molecule 1.…”
mentioning
confidence: 99%
“…7 In addition, the total synthesis of thailandepsin B (2) has been published by Cheng et al 8 and our group. 9 However, to the best of our knowledge, the total synthesis of thailandepsins D-F (4-6) has not been reported to date. In our preceding paper, 10 we developed a concise approach to study the optically pure carboxylic acid segments for the synthesis of naturally occurring bicyclic depsipeptide HDAC inhibitors.…”
mentioning
confidence: 96%